2021
DOI: 10.1177/01492063211020358
|View full text |Cite
|
Sign up to set email alerts
|

Now You See Me, Now You Don’t: A Conceptual Model of the Antecedents and Consequences of Leader Impostorism

Abstract: Impostorism, a phenomenon whereby a person perceives that the role they occupy is beyond their capabilities and puts them at risk of exposure as a “fake,” has attracted plentiful attention in the empirical literature and popular media. However, despite evidence that impostorism is frequently experienced by people in leadership positions, there has been little consideration of why this happens. In this theoretical article, we explain why formal leadership roles—roles that are characterized by elevated expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 166 publications
2
27
0
5
Order By: Relevance
“…Furthermore, with regards to impostor feelings, prior research has examined its antecedents, but has tended to focus on individual antecedents, such as attachment style or personality of individuals ( Bernard et al, 2002 ; Bravata et al, 2019 ). Our research takes a different approach, as we adhere to previous calls to examine the role of context and the workplace in shaping these experiences ( Feenstra et al, 2020a ; Kark et al, 2021 ). In doing so, we contribute to a growing body of work that shows the importance of workplace context in shaping women’s impostor feelings ( Muradoglu et al, 2022 ; Vial et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, with regards to impostor feelings, prior research has examined its antecedents, but has tended to focus on individual antecedents, such as attachment style or personality of individuals ( Bernard et al, 2002 ; Bravata et al, 2019 ). Our research takes a different approach, as we adhere to previous calls to examine the role of context and the workplace in shaping these experiences ( Feenstra et al, 2020a ; Kark et al, 2021 ). In doing so, we contribute to a growing body of work that shows the importance of workplace context in shaping women’s impostor feelings ( Muradoglu et al, 2022 ; Vial et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We considered participants’ age (in years), educational level (1 = did not complete high school, 2 = high school, 3 = some college, 4 = bachelor degree, 5 = master degree, 6 = advanced graduate work or PhD), management level (1 = lower, 2 = medium, 3 = top), number of employees they supervised (1 = no, 2 = 1–5, 3 = 6–10, 4 = 11–15, 5 = 16–20, 6 = more than 20), hierarchical power level (from 1[bottom] to 100 [top]; Lammers et al, 2010 ), and the gender dominance of the sector in which they worked (dummy coded; dummy 1 [0 = mixed/female-dominated, 1 = male-dominated] and dummy 2 [0 = mixed/male-dominated and 1 = female-dominated]; Mroczek-Dąbrowska and Gaweł, 2020 ), as potential control variables as previous research suggested that these are associated with our outcome variables ( Thompson et al, 2000 ; Vergauwe et al, 2014 ; Cokley et al, 2015 ; Feenstra et al, 2020a ; Kark et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Critically, certain organizational contextual factors conspire toward impostorism, particularly when the prescribed tasks of a given role are highly visible and entail heavy responsibility (Kark et al, 2021), as would be the case for allyship. For example, toxic learning and workplace cultures, environments of secrecy (i.e., hiding mistakes), and low psychological safety (Atherley & Meeuwissen, 2020) set the stage for sentiments of impostorism.…”
Section: Theory and Hypothesesmentioning
confidence: 99%